EXPERIENCE IN PRE-BREEDING FOR QUANTITATIVE RESISTANCE TO LATE BLIGHT IN POTATO – A REVIEW - Darsow, Ulrich (Potato Journal, 2017)
ABSTRACT: Pre-breeding for quantitative late blight resistance of potato is variety-breeding in principle, in which foliage and tuber blight resistance take precedence over all other traits; the resistance is utilized from diverse wild potato clones. A broad basis of very different pre-breeding clones is bred and retained as cross parents for crossing resistant x resistant. Progress in re-establishing of genome for cultural traits and preserving of high level of polygenic determined late blight resistance at the same time requires consideration of all traits, combination breeding for these and minimizing of backcrosses. Results are given mainly for particular difficult combining with early maturity in long-day conditions and for applied selection system.Vertical distance of AUDPC to linear regression line with maturity is a correct criterion of true quantitative foliage-blight resistance in long-day condition. Slow progress in combining of polygenic determined traits is shown. Breeding strategy is explained and problems are discussed, solutions are indicated. That pre-breeding is a very difficult breeding task, requiring highest level of special experience and a stable very long-term concept in public control. Saving of one third of current oomycide application is at least expected by new varieties.